Effect of Natural Nanostructured Rods and Platelets on Mechanical and Water Resistance Properties of Alginate-Based Nanocomposites - Huang, Dajian; Zhang, Zhuo; Ma, Zonghong; Quan, Qiling (Frontiers in Chemistry, 2018)
A series of biopolymer-based nanocomposite films were prepared by incorporating natural one-dimensional (1D) palygorskite (PAL) nanorods and two-dimensional (2D) montmorillonite (MMT) nanoplatelets into sodium alginate (SA) film by a simple solution casting method. The effect of different dimensions of nanoclays on the mechanical, water resistance, and light transmission properties of the SA/PAL or MMT nanocomposite films were studied. The field-emission scanning electron microscopy (FE-SEM) result showed that PAL can disperse better than MMT in the SA matrix in the case of the same addition amount. The incorporation of both PAL and MMT into the SA film can enhance the tensile strength (TS) and water resistance capability of the film. At a high content of nanoclays, the SA/PAL nanocomposite film shows relatively higher TS and better water resistance than the SA/MMT nanocomposite film. The SA/MMT nanocomposite films have better light transmission than SA/PAL nanocomposite film at the same loading amount of nanoclays. These results demonstrated that 1D PAL nanorods are more suitable candidate of inorganic filler to improve the mechanical and water resistance properties of biopolymers/nanoclays nanocomposites.